Light-transmitting polymer composite material as well as preparation method and application thereof

By using polymers with side chains containing tetrastyrene structure as light down conversion material in photovoltaic modules, the problem of low responsiveness of photovoltaic modules in the ultraviolet light region is solved, and efficient photovoltaic energy conversion and stable photovoltaic performance are achieved.

CN119899452AActive Publication Date: 2025-04-29CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202311388801.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-25
Publication Date
2025-04-29
Estimated Expiration
2043-10-25

AI Technical Summary

Technical Problem

The existing photovoltaic modules have low responsiveness and utilization in the ultraviolet light region, and the commonly used light-down conversion materials have poor dispersion, low quantum efficiency and unstable in polymers.

Method used

A polymer with a side chain containing a tetrastyrene structure is used as a light-down conversion material, uniform dispersion is achieved through good compatibility with the light-transmitting matrix resin, and the high luminous intensity and stability of the material are ensured through specific preparation methods such as physical blending, solution blending, etc.

Benefits of technology

The external quantum efficiency (EQE) of photovoltaic modules in the ultraviolet light region is improved, the service life of the photovoltaic packaging film is extended, and the high light transmittance is maintained, avoiding the loss of visible light.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119899452A_ABST
    Figure CN119899452A_ABST
Patent Text Reader

Abstract

The invention provides a light-transmitting polymer composite material as well as a preparation method and application thereof. The light down-conversion material adopted by the invention can be uniformly dispersed in the light-transmitting matrix resin on the premise of not influencing the light transmittance of the sheet, and can keep high luminous intensity and stability. According to the invention, the light-transmitting polymer composite material is applied to the photovoltaic packaging adhesive film, so that the responsiveness and the external quantum efficiency of an ultraviolet region of a photovoltaic module can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of photovoltaic component materials, and in particular relates to a light-transmitting polymer composite material, a preparation method and an application in a photovoltaic encapsulation film. Background Art

[0002] Photovoltaic cells use solar energy to generate electricity. When the incident wavelength energy matches the band gap of the photovoltaic cell, the cell's responsiveness to that wavelength and the corresponding current output capacity will be better. When the incident wave energy is much higher than the solar band gap energy (such as ultraviolet light with a wavelength <400nm), the excess energy tends to be converted into heat energy and promote carrier recombination, affecting the generation of current. Therefore, the responsiveness and utilization rate of common photovoltaic cells on the market, such as polycrystalline silicon photovoltaic cells, cadmium telluride (CdTe), copper indium gallium selenide (CIGS) thin-film cells, and perovskite photovoltaic cells, in the ultraviolet region are very low.

[0003] In addition, ultraviolet rays can also affect the stability of photovoltaic modules and reduce their service life. Ethylene vinyl acetate (EVA) is the most commonly used photovoltaic encapsulation film material. Because this type of film is sensitive to ultraviolet rays, ultraviolet light absorbers are usually added to the film commercially. Under the action of ultraviolet light absorbers, ultraviolet radiation is converted into heat and is not used. If ultraviolet light can be converted into visible light with lower energy, it can be effectively used for power generation.

[0004] The existing technology tends to introduce light down conversion (LDS) materials above the light absorbing layer of the photovoltaic module (for example, the upper layer, the inside of the packaging glass or the inside of the packaging film) to absorb ultraviolet rays and emit visible light with lower energy, thereby increasing the stability and utilization rate of the photovoltaic device in this wavelength band. This is to take advantage of the property that the light conversion material can absorb short-wavelength light and emit long-wavelength light.

[0005] Traditional light-conversion materials (particles) include fluorescent small molecules, rare earth materials, and inorganic quantum dots. However, the stability of fluorescent small molecules and rare earth materials is generally not high, and they are often quenched during use, with a service life of about 2 years at most; although inorganic quantum dots have good light stability, their low dispersibility and low quantum efficiency in polymers have always been difficult to solve. In addition, all three materials belong to aggregated fluorescence quenching (ACQ) materials - light conversion particles usually emit strong light when they exist as isolated molecules, but when they aggregate (under high concentration / film state / solid state conditions), non-radiative energy transfer occurs between the tightly packed luminescent particles, resulting in self-quenching of fluorescence. Therefore, the loading concentration of such luminescent materials in polymers is very limited, the fluorescence intensity emitted by the particles is quite limited, and the photovoltaic efficiency increase it can bring is not large.

[0006] Compounds with aggregation-induced emission (AIE) properties emit very weak light as isolated molecules, but have high luminescence efficiency at high concentrations / film states / solid states, and are very suitable for being introduced as additives into polymer films to give them light-down conversion functions. Tetraphenylethylene and its derivatives, as typical aggregation-induced emission molecules, have the advantages of high quantum yield, easy synthesis, easy functionalization, and high stability. Tetraphenylethylene and its derivatives have a maximum absorption of incident radiation below 400 nanometers, and a maximum radiation emission at a longer wavelength in the range of 400-900 nanometers. Therefore, using such compounds as light-down conversion materials and using them in photovoltaic modules will not cause loss of visible light. Although such compounds have been widely studied in many fields, their application in the photovoltaic field is still relatively small. If tetraphenylethylene molecules are directly mixed into a light-transmitting polymer resin, the luminescence performance of the resulting polymer resin film is prone to poor uniformity, resulting in excessive local luminescence intensity; if tetraphenylethylene is modified with a surfactant, it will affect the aggregation state of the molecules in the polymer and reduce the luminescence intensity.

[0007] The prior art lacks a method to uniformly disperse light-converting particles in a polymer host while maintaining high quantum efficiency and stability. Summary of the invention

[0008] The present invention provides a light-transmitting polymer composite material, to which a light-transmitting conversion material having a long-lasting light-transmitting function is added. The light-transmitting conversion material used in the present invention can be uniformly dispersed in a light-transmitting matrix resin without affecting the light transmittance of the sheet material and can maintain high luminous intensity and stability. The present invention also provides a method for preparing the light-transmitting polymer composite material, and the light-transmitting polymer composite material can be used as a photovoltaic encapsulation film to improve the external quantum efficiency (EQE) of a photovoltaic module in the ultraviolet region for a long time.

[0009] One of the purposes of the present invention is to provide a light-transmitting polymer composite material, comprising a light-transmitting down-conversion material and a light-transmitting matrix resin, wherein the light-transmitting down-conversion material is a polymer having a tetraphenylethylene structure in the side chain.

[0010] According to the present invention, the structural formula of the light-down conversion material is

[0011]

[0012] In formula (I) or (II), R1 is independently a substituted or unsubstituted alkyl group having 2 to 20 carbon atoms, R2 to R4 are independently selected from one of H, OH, halogen, a substituted or unsubstituted alkyl group having 1 to 20 carbon atoms, and a substituted or unsubstituted aryl or aralkyl group having 6 to 30 carbon atoms, and Y is selected from at least one of a substituted or unsubstituted alkyl group or aralkyl group having 2 to 30 carbon atoms.

[0013] According to the present invention, the light down conversion material has a maximum absorption of incident radiation below 400 nanometers and a maximum emission of radiation at a longer wavelength in the range of 400 to 900 nanometers.

[0014] According to the present invention, the number average molecular weight of the light conversion material is 5,000 to 50,000, preferably 10,000 to 30,000.

[0015] According to the present invention, the light-transmitting matrix resin includes but is not limited to at least one of ethylene-octene copolymer, ethylene-vinyl acetate copolymer, ethylene-methyl acrylate copolymer, ethylene-ethyl acrylate copolymer, ethylene-vinyl acetate-based multipolymer, ethylene-methyl acrylate-based multipolymer, ethylene-ethyl acrylate-based multipolymer, ethylene-methyl methacrylate-based multipolymer, ethylene-ethyl methacrylate-based multipolymer, ethylene-α-olefin copolymer, polyvinyl butyral, polymethyl methacrylate, polyalkyl methacrylate, alkyl acrylate copolymer, hydrogenated styrene-butadiene block copolymer, styrene-ethylene / propylene-styrene block copolymer, polyurethane resin, ionomer, polysiloxane, and epoxy resin, preferably at least one of ethylene-vinyl acetate copolymer (EVA), polymethyl methacrylate (PMMA), and epoxy resin.

[0016] According to the present invention, in the light-transmitting polymer composite material, the light-conversion material accounts for 0.01-5%, preferably 0.025-1%, of the light-transmitting matrix resin by mass percentage; the light transmittance of the light-transmitting polymer composite material is 70-99%, preferably 80-95%.

[0017] According to the present invention, the light-transmitting polymer composite material may also be added with other commonly used auxiliary components in the art, for example, at least one of a cross-linking agent, an antioxidant, and a photoinitiator may be optionally added during the preparation of the light-transmitting polymer composite material. Other additives known in the art may also be contained, and the other additives may include a cross-linking aid, a flow enhancement additive, a compatibilizer, a lubricant, a dye, a flame retardant, an impact modifier, a nucleating agent, an anti-blocking agent (such as silicon dioxide), a heat stabilizer, a dispersant, a surfactant, a chelating agent, a coupling agent, and a reinforcing additive (such as glass fiber, filler, etc.).

[0018] The second object of the present invention is to provide a method for preparing the above-mentioned light-transmitting polymer composite material, comprising the step of mixing components including the light-transmitting down-conversion material and a light-transmitting matrix resin, wherein, in terms of mass percentage, the light-transmitting down-conversion material is 0.01-5%, preferably 0.025-1% of the light-transmitting matrix resin.

[0019] The present invention has no particular limitation on the manner in which the light-down conversion material is added to the light-transmitting matrix resin for mixing, and the commonly used mixing manners in the art can be adopted, such as physical blending, melt blending, solution blending, etc. When physical blending or melt blending is adopted, the blending process conditions are not particularly limited, and the light-down conversion material and the light-transmitting matrix resin can be mixed evenly. When the solution blending method is adopted, the light-down conversion material and the light-transmitting matrix resin are added to a solvent and mixed evenly, and then the solvent is removed to obtain a light-transmitting polymer composite material, wherein the solvent used for the solution blending is not particularly limited, and the light-transmitting matrix resin can be dissolved, for example, alcohols, ketones, aromatic hydrocarbons, chlorinated hydrocarbons, dioxane, tetrahydrofuran, etc. For a high molecular polymer that has fluidity in the initial state, such as an epoxy resin before curing, the light-down conversion material can be directly mixed therein by physical blending.

[0020] According to the present invention, the preparation method of the light-down conversion material comprises: mixing polymerizable monomers including a tetraphenylethylene derivative and an optional second polymerizable monomer, and reacting them under the action of an initiator to obtain the light-down conversion material.

[0021] According to the present invention, the structural formula of the tetraphenylethylene derivative is:

[0022]

[0023] In formula (III), R′1 is a substituted or unsubstituted olefin group having 2 to 20 carbon atoms, and R′2 to R′4 are independently selected from H, OH, halogen, a substituted or unsubstituted alkyl group having 1 to 20 carbon atoms, or a substituted or unsubstituted aryl or aralkyl group having 6 to 30 carbon atoms; preferably, the tetraphenylethylene derivative is selected from at least one of tetraphenylethylene acrylate, (2-(4-((4-vinylbenzyl)oxy)phenyl)ethylene-1,1,2-triphenyl)ethylene, and [1-(4-vinylphenyl)-1,2,2-triphenyl]ethylene.

[0024]

[0025]

[0026] According to the present invention, the second polymerizable monomer is selected from at least one of styrenes, vinyl pyrrolidone, vinyl acetates, vinyl caprolactam, vinyl ethers, (meth)acrylic acid, methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, lauryl (meth)acrylate, 2-ethylhexyl (meth)acrylate, octadecyl (meth)acrylate, cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, benzyl (meth)acrylate, phenyl (meth)acrylate, and maleic anhydride.

[0027] According to the present invention, in the method for preparing the light-down conversion material: the tetraphenylethylene derivative accounts for 5 to 100 wt % of the total weight of the polymerized monomers, preferably 10 to 100 wt %.

[0028] According to the present invention, in the method for preparing the light-down conversion material:

[0029] An organic solvent is also added to the reaction, and the organic solvent is selected from at least one of dioxane, acetone, tetrahydrofuran, aromatic hydrocarbons, and chlorinated hydrocarbons, preferably at least one of dioxane, toluene, xylene, trimethylbenzene, chloroform, dichloromethane, and tetrachloroethane;

[0030] The reaction is carried out under a protective gas atmosphere, for example, under a nitrogen atmosphere;

[0031] The reaction temperature is 25 to 110°C, preferably 65 to 100°C;

[0032] The reaction time is 6 to 48 hours, preferably 8 to 24 hours;

[0033] After the reaction, the steps of filtering and drying the product after precipitation are also included, wherein the precipitation method can adopt the precipitation method commonly used in the art, such as adding a poor solvent for the light conversion material for precipitation; the drying operation can adopt the drying equipment and drying conditions commonly used in the art.

[0034] According to the present invention, the synthesis method of the light-down conversion material can be selected according to the type of monomer, including but not limited to active radical polymerization, atom transfer radical polymerization (ATRP), nitroxide stabilized radical polymerization (NMP), reversible addition-fragmentation chain transfer polymerization (RAFT), xanthate exchange radical polymerization (MADIX), iodine atom transfer radical polymerization (ITP), reversible catalytic chain transfer radical polymerization (RCTP), cobalt-mediated radical polymerization (CMRP), organic heteroatom-mediated radical polymerization (OHMRP), preferably active radical polymerization or reversible addition-fragmentation chain transfer polymerization (RAFT). Wherein, the initiator added during the reaction is not particularly limited, and the initiator commonly used in the art can be used. For example, the initiator is selected from at least one of peroxide initiators, azo initiators, and persulfate initiators, preferably at least one of benzoyl peroxide (BPO), azobisisobutyronitrile (AIBN), and potassium persulfate. The chain transfer agent required for reversible addition-fragmentation chain transfer polymerization (RAFT) polymerization is not particularly limited, and can be selected from at least one of 2-cyano-2-propyl dodecyl trithiocarbonate, 2-(dodecyl trithiocarbonate)-2-methylpropionic acid, cyanomethyl (3,5-dimethyl-1H-pyrazole)-dithioester, 2'-cyanobutyl-2'-yl 3,5-dimethylpyrazole-1-dithiocarbonate, 2-[[(butylthio)thiooxymethyl]thio]-propionic acid, 1,4-phenylenebis(methylene)didodecylbis-trithiocarbonate, 4-cyano-4-(phenylthioformylthio)pentanoic acid, 2,2'-[methylthiobis(thio)]bis[2-methylpropionic acid], and benzyl n-butyl trithiocarbonic acid.

[0035] In the present invention, when the tetraphenylethylene derivative is used as a repeating unit of the light-converting material polymer, the aggregate of the tetraphenylethylene derivative units in a single polymer molecule can realize the light-converting function, and the luminous intensity is guaranteed. When the other copolymerized units (Y repeating unit in formula (I)) in the light-converting material polymer have good compatibility with the light-transmitting matrix resin, the light-converting material polymer added as an additive to the light-transmitting matrix resin can be uniformly dispersed in the main body of the light-transmitting matrix resin and can maintain high luminous intensity and stability.

[0036] A third object of the present invention is to provide an application of the above-mentioned light-transmitting polymer composite material or the light-transmitting polymer composite material obtained by the above-mentioned preparation method in a photovoltaic encapsulation film.

[0037] The light-transmitting polymer composite material containing the light-conversion material with light-conversion function provided in the present invention can be added to the photovoltaic encapsulation film to improve the responsiveness or external quantum efficiency (EQE) of the photovoltaic module in the ultraviolet region, thereby reducing the use of ultraviolet absorbers.

[0038] Beneficial effects of the present invention:

[0039] (1) In the light-transmitting polymer composite material provided by the present invention, the light-converting material is a high molecular polymer, which has good compatibility with the light-transmitting matrix resin, and the light-converting material can be evenly dispersed in the matrix resin.

[0040] (2) The commonly used light-down conversion fluorescent small molecules and inorganic quantum dots in the prior art mostly have the characteristics of aggregated fluorescence quenching, and their luminous efficiency and intensity are easily affected by the dispersion of small molecules / inorganic quantum dots in the resin body. The light-down conversion function of commonly used fluorescent small molecules / inorganic quantum dots is very unstable during later use. The light-down conversion material structure used in the present invention contains an aggregated tetraphenylethylene structure, which has aggregation-induced emission characteristics (AIE). The light-down conversion material has high luminous efficiency in the cluster state and more stable performance.

[0041] (3) The light stability of the light conversion material used in the present invention is significantly better than that of commonly used fluorescent small molecules. The photovoltaic encapsulation film containing the light conversion material has a longer service life than other films with light conversion functions in the prior art.

[0042] (4) The light-conversion material used in the present invention has a maximum absorption of incident radiation below 400 nanometers and a maximum radiation emission at a longer wavelength in the range of 400 to 900 nanometers. Therefore, when used in a photovoltaic module, the light-conversion material will not cause loss of visible light (does not absorb the visible light part).

[0043] (5) The light-transmitting polymer composite material provided by the present invention is used as a photovoltaic encapsulation film to effectively improve the efficiency and stability of photovoltaic modules.

[0044] (6) The light-transmitting polymer composite material provided by the present invention has a simple preparation process, low cost, and broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 This is a picture of the light-transmitting polymer composite material prepared in Example 1 under ultraviolet light.

[0046] Figure 2 This is the emission spectrum of the light-transmitting polymer composite material prepared in Example 1 at an excitation wavelength of 375 nm.

[0047] Figure 3 These are the external quantum efficiency (EQE) test results of the light-transmitting polymer composite material prepared in Example 9 and the light-transmitting polymer composite material prepared in Comparative Example 1. DETAILED DESCRIPTION

[0048] The present invention is described in detail below in conjunction with specific embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the contents of the present invention still fall within the scope of protection of the present invention.

[0049] The test instruments and test conditions used in the examples are as follows:

[0050] Transmittance testing instrument: UV-visible spectrophotometer Shanghai Unico UV-4802.

[0051] Battery quantum efficiency test: QE-R Quantum Efficiency Test System from Guangyan Technology.

[0052] Emission spectrum: FLS1000 fluorescence spectrometer.

[0053] The raw materials used in the examples and comparative examples, unless otherwise specified, are disclosed in the prior art, for example, they can be directly purchased or prepared according to the preparation methods disclosed in the prior art.

[0054] Example 1

[0055] Preparation of light-conversion material A - living free radical polymerization:

[0056] Weigh 0.1 g of [1-(4-vinylphenyl)-1,2,2-triphenyl]ethylene, 0.7 g of styrene, 0.2 g of maleic anhydride, 10 mg of azobisisobutyronitrile and 5 g of xylene, and add them into a two-necked bottle. Use a double-row pipe system to remove all oxygen in the system and replace it with nitrogen. Stir the reaction at 95°C for 8 hours. After the reaction is cooled to room temperature, ethanol is added to precipitate and the solid is filtered out. After washing and drying at 70°C, the product, i.e., light-conversion material A, is obtained with a number average molecular weight of 12,000.

[0057] The structural formula of the light conversion material A is:

[0058]

[0059] Preparation of light-transmitting polymer composites - solution method:

[0060] 3g of ethylene-vinyl acetate copolymer (model E282PV, manufacturer Hanwha Total Petrochemical) and 45mg of cross-linking agent 2,5-bis(tert-butylperoxy)-2,5-dimethylhexane were dissolved in tetrahydrofuran. After the solid was fully dissolved, 9mg of the above-prepared light-conversion material A (0.3wt%) was added and stirred thoroughly. After the light-conversion agent was completely dissolved, a film was spread in a culture dish, and then placed in a vacuum drying oven at 65°C for overnight to remove the solvent. The final film was a light-transmitting polymer composite material containing the light-conversion material.

[0061] The emission spectrum of the light-transmitting polymer composite material measured by FLS1000 fluorescence spectrometer is as follows: Figure 1 The fluorescence quantum yield of the above-mentioned light-transmitting polymer composite film measured by the device was 43%.

[0062] The obtained light-transmitting polymer composite material film was sandwiched between two ultra-white glass sheets and hot-pressed at 140° C. for 40 minutes. The test showed that the light transmittance of the film in the visible light was 91%.

[0063] Example 2

[0064] Preparation of light-conversion material B - living free radical polymerization:

[0065] Weigh 0.1 g of [1-(4-vinylphenyl)-1,2,2-triphenyl]ethylene, 0.6 g of methyl methacrylate, 0.2 g of styrene, 10 mg of azobisisobutyronitrile and 5 g of dioxane, and add them to a two-necked bottle. Use a double-row pipe system to remove all oxygen in the system and replace it with nitrogen. Stir the reaction at 85°C for 9 hours. After the reaction is cooled to room temperature, ethanol is added to precipitate and the solid is filtered out. After washing and drying at 70°C, the product, i.e., light-conversion material B, is obtained with a number average molecular weight of 18,000.

[0066] The structural formula of the light conversion material B is:

[0067]

[0068] Preparation of light-transmitting polymer composites:

[0069] The preparation process of Example 1 was followed, except that the added light-down conversion material A was replaced by light-down conversion material B. The fluorescence quantum yield of the obtained light-transmitting polymer composite film was tested to be 46%, and after being sandwiched between two ultra-white glass sheets and hot-pressed at 140° C. for 40 minutes, the light transmittance of the film in the visible light was 90%.

[0070] Embodiment 3:

[0071] Preparation of photoconversion material C - reversible addition-fragmentation chain transfer polymerization (RAFT):

[0072] Weigh 0.4g of [1-(4-vinylphenyl)-1,2,2-triphenyl]ethylene, 40mg of chain transfer agent 2-cyano-2-propyl dodecyl trithiocarbonate, 4mg of azobisisobutyronitrile and 2ml of dioxane, and add them to the reaction bottle to mix. Use a double-row pipe system to remove oxygen in the system and replace it with nitrogen, stir and react at 75°C for 24 hours, and after the reaction is cooled to room temperature, add n-hexane to precipitate and filter out the solid, wash and dry it at 70°C overnight to obtain the product, that is, the light conversion material C, with a number average molecular weight of 20,000.

[0073] The structural formula of the light conversion material C is:

[0074]

[0075] Preparation of light-transmitting polymer composites:

[0076] The preparation process of Example 1 was followed, except that the added light-down conversion material A was replaced by light-down conversion material C. The fluorescence quantum yield of the obtained light-transmitting polymer composite film was tested to be 68%, and after being sandwiched between two ultra-white glass sheets and hot-pressed at 140° C. for 40 minutes, the light transmittance of the film in the visible light was 86%.

[0077] Embodiment 4-8

[0078] Preparation of light-transmitting polymer composites:

[0079] The preparation process of Example 1 is the same, except that the added light conversion material A accounts for 0.1%, 0.2%, 0.3%, 0.4% and 0.5% of the weight of the matrix resin. The fluorescence quantum yields of the obtained light-transmitting polymer composite film are 44%, 44%, 45%, 45% and 43% respectively. After being sandwiched between two ultra-white glass sheets and hot-pressed at 140°C for 40 minutes, the light transmittance of the film in the visible light is 90%, 90%, 89%, 87% and 85% respectively.

[0080] Example 9

[0081] Preparation of light-transmitting polymer composites - physical blending method:

[0082] Dissolve 10 mg of light conversion material A in 1 ml of tetrahydrofuran, and after fully dissolved, drop it into 20 g of uncured epoxy resin liquid. Place the epoxy resin liquid in a 65°C oil bath, stir for 20 minutes, and then ultrasonicate for 30 minutes to remove the solvent and allow the light conversion material A to be fully dispersed to obtain a light conversion agent epoxy resin mixed liquid. Place the obtained mixed liquid in a vacuum degassing machine, evacuate and stir for 3 to 5 minutes, then pour the mixed liquid into a culture dish to lay a film, and cure it with a UV curing lamp for 2 minutes to obtain a light-transmitting polymer composite film containing the light conversion material.

[0083] The fluorescence quantum yield of the obtained light-transmitting polymer composite film is 46%, and the light transmittance of the film in the visible light is 93%.

[0084] Example 10

[0085] Preparation of light-transmitting polymer composites - melt blending method:

[0086] 10 parts by weight of light conversion material A and 90 parts by weight of ethylene-vinyl acetate copolymer (model E282PV, manufacturer Hanwha Total) were mixed evenly at a melt flow rate of 20g / 10min, extruded by a screw extruder at 80°C and 150r / min, and water-cooled and granulated to prepare a master batch of light conversion material. 5 parts by weight of light conversion material master batch, 190 parts by weight of ethylene-vinyl acetate copolymer, 2.85 parts by weight of crosslinking agent 2,5-bis(tert-butylperoxy)-2,5-dimethylhexane, 0.3 parts by weight of N,N'-m-phenyl bismaleimide co-crosslinking agent and 0.8 parts by weight of tris(nonylphenyl)phosphite antioxidant were taken, mixed evenly, added to a casting machine, plasticized and extruded at 80°C, stretched, pulled, and rolled to form a light-transmitting polymer composite film with a thickness of 0.8mm. The fluorescence quantum yield of the obtained film is 45%, and the light transmittance of the film in the visible light is 89%.

[0087] Embodiment 11

[0088] Preparation of light-transmitting polymer composites - solution blending method:

[0089] Dissolve 10 mg of the photoconversion material A in 1 ml of tetrahydrofuran, and after fully dissolving, add it dropwise to a reaction bottle containing 10 ml of methyl methacrylate. Add 50 mg of the photoinitiator trimethylbenzoyl-diphenylphosphine oxide (TPO) to the reaction bottle, and then ultrasonically treat the reaction bottle for 30 minutes to fully disperse the photoinitiator and the photoconversion agent. Then pour the liquid in the reaction bottle into a culture dish to lay a film, and after curing with an ultraviolet curing lamp for 2 hours, a light-transmitting polymethyl methacrylate film containing the photoconversion material is obtained. The fluorescence quantum yield of the obtained light-transmitting polymer composite film is 46%, and the light transmittance of the film in the visible light is 91%.

[0090] Comparative Example 1

[0091] An epoxy resin solution without adding a light conversion material is used as Comparative Example 1.

[0092] The epoxy resin liquid without adding the light conversion material (blank epoxy resin liquid) of comparative example 1 and the epoxy resin mixed liquid containing the light conversion material obtained in example 9 were evenly spread on the silicon cell and irradiated with ultraviolet light for 2 minutes to cure the epoxy resin. The results obtained by the QE-R spectral response test system showed that (see Figure 3), the silicon cell containing light conversion material in Example 9 has a higher external quantum efficiency (EQE) and a higher responsiveness in the ultraviolet region.

[0093] Comparative Example 2

[0094] 3g of ethylene-vinyl acetate copolymer (matrix resin) (model E282PV, manufacturer Hanwha Total Petrochemical) and 45mg of cross-linking agent 2,5-bis(tert-butylperoxy)-2,5-dimethylhexane were dissolved in tetrahydrofuran, and after the solid was fully dissolved, 9mg of [1-(4-vinylphenyl)-1,2,2-triphenyl]ethylene (tetraphenylethylene derivative monomer) was added and stirred thoroughly. After it was completely dissolved, a film was laid in a culture dish, and then placed in a vacuum drying oven at 65°C to dry overnight to remove the solvent. The final film obtained is a light-transmitting polymer material containing a tetraphenylethylene derivative monomer. The fluorescence quantum yield of the film was measured to be less than 18% using FLS1000. After the obtained light-transmitting polymer material film was hot-pressed at 140°C for 40 minutes, the visible light transmittance was less than 86%. In contrast, the light-transmitting polymer composite film obtained using the light-down conversion material A in Example 1 has higher luminous quantum efficiency and transmittance.

Claims

1. A light-transmitting polymer composite material, comprising a light-transmitting down-conversion material and a light-transmitting matrix resin, wherein the light-transmitting down-conversion material is a polymer having a tetraphenylethylene structure in the side chain.

2. The light-transmitting polymer composite material according to claim 1, characterized in that: The structural formula of the light-down conversion material is: In formula (I) or (II), R1 is independently a substituted or unsubstituted alkyl group having 2 to 20 carbon atoms, R2 to R4 are independently selected from one of H, OH, halogen, a substituted or unsubstituted alkyl group having 1 to 20 carbon atoms, and a substituted or unsubstituted aryl or aralkyl group having 6 to 30 carbon atoms, and Y is selected from at least one of a substituted or unsubstituted alkyl group or aralkyl group having 2 to 30 carbon atoms; and / or, The number average molecular weight of the light conversion material is 5,000 to 50,000, preferably 10,000 to 30,000.

3. The light-transmitting polymer composite material according to claim 1, characterized in that: The light-transmitting matrix resin is selected from at least one of ethylene-octene copolymers, ethylene-vinyl acetate copolymers, ethylene-methyl acrylate copolymers, ethylene-ethyl acrylate copolymers, ethylene-vinyl acetate-based multi-polymers, ethylene-methyl acrylate-based multi-polymers, ethylene-ethyl acrylate-based multi-polymers, ethylene-methyl methacrylate-based multi-polymers, ethylene-ethyl methacrylate-based multi-polymers, ethylene-α-olefin copolymers, polyvinyl butyral, polymethyl methacrylate, polyalkyl methacrylate, alkyl acrylate copolymers, hydrogenated styrene-butadiene block copolymers, styrene-ethylene / propylene-styrene block copolymers, polyurethane resins, ionomers, polysiloxanes, and epoxy resins, and is preferably selected from at least one of ethylene-vinyl acetate copolymers, polymethyl methacrylate, and epoxy resins.

4. The light-transmitting polymer composite material according to claim 1, characterized in that: In terms of mass percentage, the light conversion material is 0.01 to 5%, preferably 0.025 to 1%, of the light-transmitting matrix resin; and / or, The light transmittance of the light-transmitting polymer composite material is 70 to 99%, preferably 80 to 95%.

5. A method for preparing the light-transmitting polymer composite material according to any one of claims 1 to 4, comprising the step of mixing components including the light-down conversion material and a light-transmitting matrix resin.

6. The preparation method according to claim 5, characterized in that: In terms of mass percentage, the light down conversion material accounts for 0.01-5% of the light-transmitting matrix resin, and preferably 0.025-1%.

7. The preparation method according to claim 5, characterized in that: The preparation method of the light-down conversion material comprises: mixing polymerizable monomers including tetraphenylethylene derivatives and optional second polymerizable monomers, and reacting them under the action of an initiator to obtain the light-down conversion material.

8. The preparation method according to claim 7, characterized in that: The structural formula of the tetraphenylethylene derivative is: In formula (III), R′1 is a substituted or unsubstituted olefin group having 2 to 20 carbon atoms, and R′2 to R′4 are independently selected from H, OH, halogen, a substituted or unsubstituted alkyl group having 1 to 20 carbon atoms, or a substituted or unsubstituted aryl or aralkyl group having 6 to 30 carbon atoms; preferably, the tetraphenylethylene derivative is selected from at least one of tetraphenylethylene acrylate, (2-(4-((4-vinylbenzyl)oxy)phenyl)ethylene-1,1,2-triphenyl)ethylene, and [1-(4-vinylphenyl)-1,2,2-triphenyl]ethylene; and / or, The second polymerizable monomer is selected from at least one of styrenes, vinyl pyrrolidone, vinyl acetate, vinyl caprolactam, vinyl ethers, (meth)acrylic acid, methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, lauryl (meth)acrylate, 2-ethylhexyl (meth)acrylate, octadecyl (meth)acrylate, cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, benzyl (meth)acrylate, phenyl (meth)acrylate, and maleic anhydride; and / or, The initiator is selected from at least one of peroxide initiators, azo initiators, and persulfate initiators, preferably at least one of benzoyl peroxide, azobisisobutyronitrile, and potassium persulfate; and / or, The tetraphenylethylene derivative accounts for 5 to 100 wt %, preferably 10 to 100 wt %, of the total weight of the polymerized monomers.

9. The preparation method according to claim 7, characterized in that: An organic solvent is further added to the reaction, wherein the organic solvent is selected from at least one of dioxane, acetone, tetrahydrofuran, aromatic hydrocarbons, and chlorinated hydrocarbons, preferably at least one of dioxane, toluene, xylene, trimethylolbenzene, chloroform, dichloromethane, and tetrachloroethane; and / or, The reaction is carried out under a protective gas atmosphere; and / or, The reaction temperature is 25 to 110° C., preferably 65 to 100° C.; and / or, The reaction time is 6 to 48 hours, preferably 8 to 24 hours; and / or, After the reaction, the method further comprises the steps of filtering and drying the product after precipitation.

10. Use of the light-transmitting polymer composite material according to any one of claims 1 to 4 or the light-transmitting polymer composite material obtained by the preparation method according to any one of claims 5 to 9 in photovoltaic encapsulation films.

Citation Information

Patent Citations

  • Under-wavelength transfer material as well as preparation method and application thereof

    CN103274965A

  • Light conversion film for green dye containing agglomeration-induced emission (AIE) properties

    CN106811191A

  • Ethylene copolymer and preparation method and application thereof

    CN113717304A

  • Stemming material for rock blasting

    KR1020250045201A